Ratcheting life prediction of quenched–tempered 42CrMo4 steel - Kreethi R.; Sivateja C.; Mondal A.K.; Dutta K. (My University, 2025)
A series of ratcheting tests on quenched–tempered 42CrMo4 steel with varying combinations of mean stresses and stress amplitudes were conducted at room temperature till failure. The ratcheting lives of the steel at different stresses were estimated using a few existing stress-based life prediction equations. A stress-based life prediction model was newly proposed. The experimental results revealed that ratcheting strain monotonically increased with mean stress and stress amplitude for all employed test parameters. The steel showed predominantly cyclic softening feature. The newly proposed model predicted ratcheting life efficiently in the life range of 102–104 cycles with a life factor of 1. It also efficiently predicted the fatigue life of other materials. Fractographic examinations revealed the standard fatigue fracture features. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.